The effect of IT governance on business resilience with intellectual capital as mediating variable - Hapsari, Ira; Praptapa, Agung; Lestari, Puji; Herwiyanti, Eliada (Kompartemen : Jurnal Ilmiah Akuntansi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) must continue to adapt in today’s rapidly changing digital business climate to become resilient organizations and maintain their competitive advantage. This study examines the relationship between IT governance (ITG), intellectual capital (IC), and business resilience (BR). Data were collected from 100 MSMEs in Banyumas, Central Java. Specifically, the researcher investigated how IC mediates the effect of ITG on business resilience. The study used a causal step analysis method. The results showed that ITG has a positive effect on business resilience. ITG can improve IC and strengthen business resilience. This mediation suggests that building intellectual capital can increase the benefits of IT and make companies stronger. This knowledge is valuable for MSME managers and policy makers to improve organizational resilience through ITG strategies and IC development.